Do Networks Do the Works? Towards Recognising (and Solving) a Migration-Entrepreneurship Conundrum - Nestorowicz, Joanna (Central and Eastern European Migration Review, 2013)
On the one hand, research shows that immigrant entrepreneurs find support for their business among other immigrants, within immigrant enclaves. On the other hand, the economic theory of industrial organisation clearly suggests that business concentration is detrimental to profits, which in turn creates disincentives for potential newcomers. This article aims to find an answer to this conundrum. It asks three questions: is business competition present at all among immigrants? If yes, then is it the market mechanism that reconciles the existence of immigrant business solidarity with immigrant business competition? And what determines the fine line between generating positive and negative externalities for other immigrant businesses? Through an analysis of migration networks among immigrant businessmen, this research concludes that both processes might in fact occur. The factor that determines whether it is one or the other is the specificity of the industry in which a given business operates.
Keywords: competition; entrepreneurship; immigration; industrial organisation; migration networks